2001
DOI: 10.1093/jhered/92.1.38
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Wild and Cultivated Sunflower for Breeding Purposes by AFLP Markers

Abstract: Amplified fragment length polymorphisms (AFLPs) represent one of the most powerful polymerase chain reaction (PCR)-based markers which enables one to discriminate single plants by DNA analysis. To date this technique has only been applied in cultivated sunflower to detect genetic diversity among oilseed inbred lines. In this article we report the use of AFLP markers to investigate the level of diversity within and between populations of Helianthus argophyllus collected in the Maputo area, Mozambique, both for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
12
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 13 publications
4
12
0
Order By: Relevance
“…These RAPD variations were consistent with some earlier reports (Doetz et al, 1993(Doetz et al, , 1994El Gengaihi et al, 2009), and also were compatible with those RAPD results reported in sunflower (e.g., see Lawson et al, 1994) and those detected by other markers (e.g., see Quagliaro et al, 2001;Wangsomnuk et al, 2006). Such large RAPD variation is expected (Hamrick and Godt, 1998), as Jerusalem artichoke is an outcrossing, hexaploidy (2n = 6x = 102) plant (Swanton et al, 1992).…”
Section: Rapd Variationsupporting
confidence: 92%
“…These RAPD variations were consistent with some earlier reports (Doetz et al, 1993(Doetz et al, , 1994El Gengaihi et al, 2009), and also were compatible with those RAPD results reported in sunflower (e.g., see Lawson et al, 1994) and those detected by other markers (e.g., see Quagliaro et al, 2001;Wangsomnuk et al, 2006). Such large RAPD variation is expected (Hamrick and Godt, 1998), as Jerusalem artichoke is an outcrossing, hexaploidy (2n = 6x = 102) plant (Swanton et al, 1992).…”
Section: Rapd Variationsupporting
confidence: 92%
“…Such a level of polymorphism was consistent with some reports based on various molecular markers [28][29][30], and compatible with those results reported in the cultivated sunflower [46,47]. Interestingly, the overall polymorphism was compatible over the three marker types, but the SRAP marker appeared to display a slightly higher polymorphism and detect more DNA fragments with frequencies larger than 0.5.…”
Section: Marker Polymorphismsupporting
confidence: 92%
“…AFLP has been used to examine the genetic relationships among other crop species. These include potato (van Eck et al, 1995), lettuce (Hill et al, 1996), rice (Cho et al, 1996), barley (Powell et al, 1997), soybean (Keim et al, 1997), maize (Vuylsteke et al, 1999), eggplant (Mace et al, 1999), and sunflower (Quagliaro et al, 2001). Previous studies showed that an AFLP analysis has greater discriminatory power than a RAPD analysis and other genomic fingerprinting methods.…”
Section: Introductionmentioning
confidence: 99%